From perceived need to purchasing behavior: A study on the formation mechanism of consumers’ willingness to pay a premium for organic food - Zhang, Ziyu (Edelweiss Applied Science and Technology, 2025)
As food safety concerns grow increasingly prominent, consumers are placing greater emphasis on health, nutrition, and sustainable consumption. Organic foods, with their eco-friendly and safety attributes, are gradually becoming a market focus. This paper centers on consumer behavior, drawing upon consumer behavior theory, signaling theory, and ABC theory to construct a framework for the formation mechanism of willingness to pay a premium for organic foods. The study reveals the psychological pathway through which consumers, when faced with organic foods, transform cognitive judgments and emotional attitudes into purchase intentions and premium payment decisions. This framework broadens the theoretical perspective of organic food consumption research and provides systematic theoretical support for sustainable consumption studies. While offering valuable theoretical insights, the study has certain limitations. Future research could enhance the systematicity and applied value of organic food consumption behavior studies by collecting specific sample data and conducting cross-national empirical analyses.